1986
DOI: 10.1055/s-2007-1017194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Specific Benzodiazepine Antagonist Ro 15-1788 on Sleep

Abstract: In troductionThe selective antagonistic efficacy of the benzodiazepine antagonist Ro 15-1788 is weil established. In the first clinical trials it was found that this drug could reverse the sedative-hypnotic effects of clonazepam, diazepam, flunitrazepam, midazolam, and other benzodiazepines rapidly ( see Hunkeler et al., 1981;Bonetti et al., 1982;Klotz et al., 1985). The very short duration of action corresponds weil to the elimination half-life time of about 0.97 ± 0.2 hours (Klotz et al., 1984).Most studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Isatin showed no GABA shift in its inhibition of Ro 15-1788 binding, suggesting that, in itself, it is neither strongly pro-nor anticonvulsant (Ehlert et al, 1981). However, Ro 15-1788, which also has no GABA shift, can both block seizures and reduce sleep in certain models (Scollo-Lavizzari, 1984;Ziegler et al, 1986). Whether isatin itself, or some more potent metabolites, do exert their effects as antagonist at these receptors, or act on some other system, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Isatin showed no GABA shift in its inhibition of Ro 15-1788 binding, suggesting that, in itself, it is neither strongly pro-nor anticonvulsant (Ehlert et al, 1981). However, Ro 15-1788, which also has no GABA shift, can both block seizures and reduce sleep in certain models (Scollo-Lavizzari, 1984;Ziegler et al, 1986). Whether isatin itself, or some more potent metabolites, do exert their effects as antagonist at these receptors, or act on some other system, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[176] An attempt to test the vigilance enhancing properties of flumazenil in sleep-deprived patients showed that this effect, if it existed at all, was very transient and was immediately followed by a vigilance decrement.…”
Section: Gaba-ergic Agentsmentioning
confidence: 99%
“…b-carbolines are inverse agonists, antagonists, or partial inverse agonist/antagonists. It has been hypothesized that if sleepiness is associated with increased levels of some kind of endogenous BZligand,¯umazenil's antagonism would immediately`wake up' a sleeping or sleepy person and hence maintain vigilance (Ziegler et al, 1986). An attempt to test the vigilance-enhancing properties Vermeeren, 1988).…”
Section: Gaba-ergic Mechanismsmentioning
confidence: 99%